Measurement of Audit Opinion in Supervisory Apparatus Capability and Maturity of the Government Internal Control System - Amelia Kontesa; Fikry Karim; Rahma Masdar; Masruddin Masruddin (STKIP Singkawang, 2025)
This study aims to measure audit opinion based on the capability of the government's internal control apparatus and the maturity of the government's internal control system. The test used SEM-PLS with data obtained from 34 provinces in Indonesia during the period 2018 to 2022, with a total of 1,295 data observations. This study used a quantitative approach with an explanatory research type. Data was collected through secondary documentation via official reports on APIP capability evaluations, SPIP maturity, and audit opinions published by BPKP and BPK for all local governments in Indonesia. Data collection techniques were carried out through documentation from the official websites of the relevant institutions. The data analysis technique used in this study was Partial Least Squares Structural Equation Modelling (PLS-SEM) with the help of SmartPLS software. Tests were conducted on the outer model, inner model, and significance tests through resampling (bootstrapping) to determine the relationship between variables. The study found that specifically capability had a basis in consideration of giving an audit opinion that falls into the ‘weak’ category. However, the maturity of the government's internal control system had a linear basis that was classified as ‘moderate’. Thus, it is important to pay attention to the apparatus in improving the quality and capability in reducing the risk of possible irregularities and ensuring that the implementation of governance principles leads to good governance. These findings support the development of the quality of governance in government financial audit.